A non-expensive bidimensional kinematic balance assessment can detect early postural instability in people with Parkinson’s disease - Santos, Gabriel Venas; d'Alencar, Matheus Silva; Helene, Andre Frazão; Roque, Antonio C.; Miranda, José Garcia Vivas; Piemonte, Maria Elisa Pimentel (Frontiers in Neurology, 2023)
Background: Postural instability is a debilitating cardinal symptom of Parkinson's disease (PD). Its onset marks a pivotal milestone in PD when balance impairment results in disability in many activities of daily living. Early detection of postural instability by non-expensive tools that can widely be used in clinical practice is a key factor for widespread population prevention of falls and their negative consequences. Objective: To investigate the effectiveness of a two-dimensional balance assessment to identify the decline in postural control associated with PD progression. Methods: 55 people with PD, 37 male, 11 participants in stage I, 23 in stage II, and 21 in stage III according to the H&Y rating scale, performed three clinical balance tests (Timed Up and Go, Balance Evaluation Systems Test, and Push and Release test) in addition to static stance test recorded by a two-dimensional movement analysis software. Based on kinematic variables generated by the software, a Postural Instability Index (PII) was created, allowing a comparison between its results and those obtained by clinical tests. Results: There were differences between sociodemographic variables directly related to PD evolution. Although all tests were correlated with H&Y stages, only the PII was able to differentiate the first three stages of disease evolution (H&Y I and II: p = .03; H&Y 1 and 3: p = .00001; H&Y 2 and 3: p = .02). The other clinical tests were able to differentiate only people in the moderate PD stage (H&Y III). Conclusion: Based on the PII index, it was possible to differentiate the postural control decline among the first three stages of PD evolution. This study offers a promising possibility of a low-cost, early identification of subtle changes in postural control of people with PD in clinical practice.